Efficacy of chitosan and sodium alginate scaffolds for repair of spinal cord injury in rats - Yao, Zi-ang (Neural Regen Res, 2018)
Spinal cord injury results in the loss of motor and sensory pathways and spontaneous regeneration of adult mammalian spinal cord neurons is limited. Chitosan and sodium alginate have good biocompatibility, biodegradability, and are suitable to assist the recovery of damaged tissues, such as skin, bone and nerve. Chitosan scaffolds, sodium alginate scaffolds and chitosan-sodium alginate scaffolds were separately transplanted into rats with spinal cord hemisection. Basso-Beattie-Bresnahan locomotor rating scale scores and electrophysiological results showed that chitosan scaffolds promoted recovery of locomotor capacity and nerve transduction of the experimental rats. Sixty days after surgery, chitosan scaffolds retained the original shape of the spinal cord. Compared with sodium alginate scaffolds- and chitosan-sodium alginate scaffolds-transplanted rats, more neurofilament-H-immunoreactive cells (regenerating nerve fibers) and less glial fibrillary acidic protein-immunoreactive cells (astrocytic scar tissue) were observed at the injury site of experimental rats in chitosan scaffold-transplanted rats. Due to the fast degradation rate of sodium alginate, sodium alginate scaffolds and composite material scaffolds did not have a supporting and bridging effect on the damaged tissue. Above all, compared with sodium alginate and composite material scaffolds, chitosan had better biocompatibility, could promote the regeneration of nerve fibers and prevent the formation of scar tissue, and as such, is more suitable to help the repair of spinal cord injury.